The Private Self in The Context of Prayer - Predko, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The analysis is based on the thesis that prayer is not only dialogue in the context of man-God relationship but also a kind of mental state characterized by empathy and synergy of both exclusively human and divine. The main prayer's nuance of meaning-appeal, response, insight, on the one hand, form the dialogue as an opportunity to accept the existence of God in the subjective dimension of I-You, and on the other-contribute to transcendence and self-construction of personality. In this prayer process, the perception of self as Other and Other as self is carried out. our study The purpose of the research is to find out Self-Other relationship in the context of prayer, its psychological and religious capabilities, which reveal its functional aspectsMethods. Analysis, comparison, synthesis, generalization and systematizationResults. Prayer, opening the prospects of overcoming existential problems, firstly, satisfies the spiritual needs of man through dialogue with the Deity. Secondly, it forms sensitivity to the Other. Thirdly, it performs the function of centering of consciousness, thanks to which centering individuality is transformed into an integral personality. Attention is paid to the functional relationship of faith and prayer, their role in constructing the prayer experience as a kind of empathic life strategy and as a religious and spiritual space of coexistence of I and Other. Prayer experience promotes forming the basis, life affirmation of a person and contains significant psychotherapeutic potential, as its carrier is aimed at effective and practical overcoming of the finiteness of human existence in the pursuit of eternal, absolute existence.Conclusion. Prayer as a dialogue motivates the activation of a people's essential forces, enriching their experience, personal growth and optimizing spiritual self-transcendence. Prayer intentionally contains the Other in itself, ensures co-involvement with Him. Its intensity depends on the emotional palette, which enhances the dialogue and constructs self. Prayer not only "focuses" consciousness, but also acts as a powerful means of centring it. This ability of prayer, enabling the process of unity of the human and the Divine, contributes to the formation of a harmonious, integral personality. The essence of prayer is most clearly revealed in prayer¬empathy when the boundaries of self are overcome and problems, the feelings of the Other find a response in self, a kind of personal overflow takes place. Prayer contains a significant psychotherapeutic potential, helps to overcome difficult life situations and contributes to the improvement of mental health, and during periods of life crises, ensure moral survival and affirmation of a personality.
Keywords: private self; prayer; dialogue; relationship; centering of consciousness; emotion; empathy; religious faith; prayer experience; psychotherapeutic effect